Islamic higher education: maintaining and ensuring quality - Mohd. Asraf, Ratnawati; Nair, Sheela (2009)
This paper discusses the issue of quality in higher education, specifically in Islamic Universities. It raises the issue of what we mean by quality or what we would like quality to mean, and how we can ensure and maintain quality in our higher institutions. In addressing the issue, it also discusses the IS0 9000: what it is, how it came to be applied in education, and Malaysia’s experience with the system; and raises the question of whether the institution of this system would necessarily lead to quality. The paper concludes with suggestions for ensuring and maintaining quality in Islamic Universities.